2017
DOI: 10.3390/polym9100498
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of Nanoporous Aluminum-Based Coordination Polymers as Catalysts for Selective Sulfoxidation Reaction

Abstract: A series of aluminum-based coordination polymers or metal-organic frameworks (Al-MOFs), i.e., DUT-4, DUT-5, MIL-53, NH 2 -MIL-53, and MIL-100, have been facile prepared by microwave (MW)-assisted reactions and used as catalysts for selective sulfoxidation reactions. The MW-assisted synthesis drastically reduced the reaction time from few days to hours. The prepared MOFs have smaller and uniform particle sizes and better yield compared to conventional hydrothermal method. Furthermore, the Al-MOFs have been succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
(47 reference statements)
2
15
0
Order By: Relevance
“…The phase composition of the pristine and HT DUT-4 is presented in Figure . The XRD pattern of the pristine DUT-4 is in good agreement with a previous report, proving that phase-pure DUT-4 is synthesized. After coating the hydrophobic layer, the XRD pattern remains nearly unchanged, which demonstrates that this solution-immersion process does not affect the crystal structure of DUT-4.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The phase composition of the pristine and HT DUT-4 is presented in Figure . The XRD pattern of the pristine DUT-4 is in good agreement with a previous report, proving that phase-pure DUT-4 is synthesized. After coating the hydrophobic layer, the XRD pattern remains nearly unchanged, which demonstrates that this solution-immersion process does not affect the crystal structure of DUT-4.…”
Section: Resultssupporting
confidence: 91%
“…The BET surface area (S BET ) of the pristine DUT-4 is measured to be 1183.8 m 2 •g −1 , close to the previously reported value. 46 A chemical-vapor deposition method using perfluorohexane was employed to introduce internal hydrophobicity to HKUST-1 to increase water stability. 36 However, the S BET and porosity were reduced by roughly 30%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the research by ( Vakili et al, 2018 ), microwave-assisted synthesis of Zr-MOFs only required a reaction time of 2–2.5 h, much lower than conventional solvothermal synthesis (normally 24 h). Moreover, the homogeneous effects of microwaves can create a uniform seeding condition ( Vinu et al, 2017 ), and by adjusting the microwave energy intensity, the nucleation and crystal growth rate can be easily controlled, enabling the size-controlled synthesis of MOFs. ( Liu et al, 2017 ) reported the successful microwave synthesis of micron and nanometer-sized γ-cyclodextrin MOFs (γ-CD-MOFs) for the first time.…”
Section: Controlled Synthesis Of Mofs For Food Safety Sensorsmentioning
confidence: 99%
“…It quantitatively and selectively allows facile emergence of valuable organic compounds, polymers and nanomaterials in extremely short reaction time than by applying conventional heating. [22][23][24] Additionally, the use of microwave irradiation heating offers significant energy-saving processes with low level of formation of side reactions; therefore, it accomplishes the conditions of green chemistry. Microwave heating could be designateed as a Bunsen burner of the current century, as it is predominantly used.…”
Section: Introductionmentioning
confidence: 99%